HfB2-SiC-MoSi2 oxidation resistance coating fabricated through in-situ synthesis for SiC coated C/C composites - Wang, Peipei; Li, Hejun; Ren, Xuanru; Yuan, Ruimei; Hou, Xianghui; Zhang, Yulei (Elsevier, 2017)
A brand new HfB2-SiC-MoSi2 coating was fabricated to protect carbon/carbon (C/C) composites with inner SiC coating from oxidation, which was prepared by in-situ synthesis. In this paper, the C/C substrate with the protection of the HfB2-SiC-MoSi2/SiC coating could resist oxidation in 1773 K air for 408 h. The double coating also presented expected oxidation protection performance at dynamic oxidation environment. In the test process, the surface coating was oxidized to form a self-sealing silicate glass layer containing HfO2 and HfSiO4, which could hinder crack propagation in coating.